Combination of Zeolite, Charcoal and Water Spinach as Integrated Filters to Reduce Ammonia Level in Aquaponic System - Tanaya, Fista Yohana; Kisworo; Prihatmo, Guruh (Universitas Kristen Duta Wacana, 2021)
Aquaponic is a combination of aquaculture and hydroponic plants in the recirculation system. The aquaponic system has a constraint in the form of ammonia which is produced by fish metabolism. In order to increase the productivity of fish and plants in aquaponics, an approach by integrating filters and biofilter could be used to reduce ammonia waste. The aim of this research was to study the use of zeolite, charcoal, and water spinach as components of integrated filters to reduce ammonia concentration in an aquaponic system. This research was conducted for four weeks with three repetitions of water sampling sourced from pond, filters, and output. The results of this study indicated that the use of combination of zeolite, charcoal and water spinach as componentof integrated filters can reduce ammonia throughout the research period.